Evolution of the European federal movements (Economic and Political Thought, 2018)
The article aims to examine the European federalism movements fromWorld War II until present time with respect to evolution that took place inthe field of proposed ideas, concepts and visions concerning the Europeanfederation. The elements of historical and comparative analysis made it possibleto prove that the federalists’ thought creates a coherent concept of a federalsolution for Europe. At the same time, this vision maintaining coherenceat all the stages of developing the European integration was adapted to thechanging political and economic conditions, the current state of integrationand challenges that occurred in Europe. At the same time, however, it is hardto resist the feeling that in the 1940s and 1970s, a catalogue of proposals wasformulated and they serve to develop detailed concepts and, as a result, newsolutions are rather rarely proposed.
Keywords: federalism, European federation, federal concepts of European integration, evolutionary federalism, revolutionary federalism